Does it Pay to Be Good in Developing Countries? The Relationship Between Corporate Social Responsibility and Financial Performance in Malaysia - Bala Ramasamy; Hung Woan Ting; Matthew C.Y. Yeung (Asian Academy of Management Journal of Accounting and Finance, 2007)
Corporate social responsibility (CSR) as a common business practice has only recently established a foothold in developing countries. This is evidenced by a lack of literature in the area of CSR among these countries. In Malaysia, for instance, only a third of large businesses can be considered CSR active. The purpose of this paper is to determine if there is a link between CSR performance and financial performance among these large businesses. We compare the monthly average returns of a portfolio of CSR active companies (based on disclosure) against a portfolio of inactive CSR companies as well as against the market, represented by the Kuala Lumpur Stock Exchange Composite Index (KLSE-CI). Both risk unadjusted and risk adjusted returns were utilized in this study. In either case, we do not find strong statistical evidence to show that our CSR portfolio outperforms the market; neither does it beat the non-CSR portfolio. Nevertheless, based on the results obtained by similar studies in the US, UK and Australia, there is reason to believe that CSR active companies may outperform their counterparts when consumers, employees and other stakeholders increase the value they place on socially responsible activities of a firm. Our findings also imply that international investors looking for socially responsible companies in developing companies to invest in need not incur significant opportunity costs when carrying out their investment strategies. Given that developing countries like Malaysia feature strongly in international investment portfolios like the Morgan Stanley International Composite Index (MSCI), socially responsible investors could extend their portfolios internationally without compromising their rate of returns.